IMPROVING THE VISUALIZATION OF THE GEOLOGICAL STRUCTURE OF THE HOVSAN AREA, AZERBAIJAN USING VSP - AHMADOV, Tofik; ASADLİ, Amikishi (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. Increasing the resolution (both vertical and horizontal) of land and borehole seismic exploration is an urgent task facing geophysicists. There are various ways to increase the resolution of seismic studies, among which inelastic absorption takes a special place. This method has not been widely used compared to other methods (for example, distribution of the total charge of explosives over smaller ones, i.e., grouping of sources, inverse filtering - deconvolution, etc.) due to the limited amount of information about inelastic absorption and the difficulty of determining it or the quality factor of the environment. Important information for determining the quality factor of the medium and inelastic absorption is provided by borehole seismic exploration, in particular, VSP (vertical seismic profiling). The recent VSP at well N 1856 of the Govsan area made it possible to determine the inelastic absorption of the medium from well observations and thereby restore the weakened higher frequency components of the seismic wave field, which made it possible to quite significantly change the observed wave pattern on time sections, enriching it with high frequency components and thereby increasing the resolution of surface as well as borehole seismic data. This research aims to improve the vertical resolution of land and borehole seismic exploration using vertical seismic profiling data on inelastic absorption of the geological medium. Methods. Based on the VSP data, the effective quality factor Q parameter was determined. For this purpose, the entire recorded VSP interval was divided into 4 parts. Results. The entire recorded VSP interval was divided into four parts: the full interval ( 324–4500 m measured depth) for determining the effective quality factor Q, and three sub-intervals – upper ( 324–1887 m), middle ( 1803–3799 m), and lower ( 3814–4500 m) – for calculating interval values of the quality factor. After determining Q for each interval, the average effective quality factor Q=145 was obtained and applied to restore attenuated frequencies on seismic time sections and the vertical component Z of the VSP profile. A comparison of the original and processed seismic time sections after Q=145 filtering shows significant improvements in resolution. The restoration of high-frequency components in seismic records has notably enhanced the clarity of both surface seismic and VSP time sections. The results confirm that applying VSP-derived quality factor parameters can be highly effective in land seismic data processing. Conclusions. The application of Q-filtering with an effective quality factor of Q=145 has significantly improved the resolution of both surface seismic and VSP time sections. The results demonstrate the effectiveness of utilizing certain VSP parameters in land seismic processing. Additionally, restoring attenuated high-frequency components enhances data clarity and interpretability. The use of the quality factor can be integrated at different processing stages, with its optimal application determined experimentally to achieve the best results.